Nationalism, democracy, and development : state and politics in India - Bose, Sugata; Jalal, Ayesha (Delhi ; New York : Oxford University Press, 1997)
Contributed essays.
Includes bibliographical references and index.
Keywords: Nationalism -- India; Democracy -- India